The Neuroprotective Effects of Memantine, and Curcumin after Cerebral Ischemia-reperfusion Injury in Elderly Rats - Cabalar, Murat; Altınay, Serdar; Yildirim, Funda; Celik, Duygu Sultan; Kucuk, Suat Hayri; Isler, Cihan; Isiksacan, Nilgun; Bajrami, Arsida; Gulcubuk, Ahmet (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Some researches reveal that pharmacologic and phytotherapeutic agents have benefits on neurological disorders associated with the effects of reactive oxygen species. Aim: The purpose of this research was to evaluate the protective effects of curcumin and memantine in a cerebral ischemia/reperfusion model in rats. Materials and Methods: This experimental study was conducted at the Bagcilar Training and Research Hospital, Istanbul, Turkey. Rats were separated into five experimental groups (n=8) as follows: Curcumin (Group I), Memantine (Group II), Curcumin+Memantine (Group III), ischemia (Group IV), and sham (Group V). Cerebral ischemia was performed surgically with bilateral common carotid artery occlusion for 30 min, followed by reperfusion for 72 hr. Tissue and serum samples were collected and assessed for tumor necrosis factor-α, interleukin-6, lactate dehydrogenase, catalase, glutathione peroxidase, xanthine dehydrogenase, superoxide dismutase, and malondialdehyde levels. Further, in tissue samples, both neuronal loss and caspase-3 levels were determined. Results: Serum and tissue levels of interleukin-6, tumor necrosis factor-α, malondialdehyde, and lactate dehydrogenase were found significantly lower in the Group I, II, and III compared to Group IV (p<0.001). Glutathione peroxidase, superoxide dismutase, and catalase levels in Group I, II, and III were significantly higher than those of Group IV (p<0.001). Conclusion: Curcumin, Memantine, and Curcumin+Memantine treatment were found to be efficacious in decreasing oxidative damage in cerebral ischemia but failed to prevent tissue damage.
Keywords: Brain ischemia; Curcumin; Memantine; Oxidative injury; Reperfusion